2004
DOI: 10.1007/s00405-003-0656-1
|View full text |Cite
|
Sign up to set email alerts
|

Free-flap iliac crest in mandibular reconstruction following segmental mandibulectomy for squamous cell carcinoma of the oral cavity

Abstract: The aim of the study was to asses the anatomic and functional results and quality of life of a cohort of patients submitted to immediate reconstruction with the iliac osteomusculocutaneous free flap following composite resection for carcinoma of the oral cavity. Twelve patients affected by squamous cell carcinoma of the oral cavity were submitted to a single surgical procedure that included a segmental mandibulectomy in a composite resection, followed by primary reconstruction using a vascularized bone-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…In particular, group A patients with the highest amount of the bone resection showed the worst prosthetic outcomes in terms of quantity and quality of food to eat, and speech fluidity. Similar results on masticatory ability (Gürlek et al 1998; Wilson et al 1998; Puxeddu et al 2004) and phonetics (Gürlek et al 1998; Wilson et al 1998) were found in previous investigations in reconstructed patients using a specific questionnaire. Iizuka et al (2005) compared mandibulectomy‐reconstructed patients with and without dental rehabilitation and found good oral functions as intellegible speech and normal diet in both groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, group A patients with the highest amount of the bone resection showed the worst prosthetic outcomes in terms of quantity and quality of food to eat, and speech fluidity. Similar results on masticatory ability (Gürlek et al 1998; Wilson et al 1998; Puxeddu et al 2004) and phonetics (Gürlek et al 1998; Wilson et al 1998) were found in previous investigations in reconstructed patients using a specific questionnaire. Iizuka et al (2005) compared mandibulectomy‐reconstructed patients with and without dental rehabilitation and found good oral functions as intellegible speech and normal diet in both groups.…”
Section: Discussionsupporting
confidence: 89%
“…The advent of endosseous implants offered a great contribution to the recovery of adequate mastication, speech and swallowing. Fixed implant-supported prosthetic rehabilitation in the reconstructed mandible seems to provide good functional outcomes and general well-being (Weischer et al 1996;Curtis et al 1997;Gü rlek et al 1998;Wilson et al 1998;Mü ller et al 2004;Teoh et al 2005), with an implant survival rate about 90-95% (Chan et al 1997;Marunick & Roumanas 1999;Weischer & Mohr 1999;Chiapasco et al 2000;Cheung & Leung 2003;Puxeddu et al 2004).…”
mentioning
confidence: 99%
“…It has been demonstrated that small soft-tissue defects in the oral cavity and oropharynx primarily yield better post-operative functional outcomes when closed compared with flap reconstruction [32]. Segmental mandibulectomy with free-flap iliac crest reconstruction for oral cavity cancer yields better results with respect to multiple QOL domains, including physical wellbeing, socio-family relationships, chewing and swallowing when compared with no mandibular reconstruction [33]. Segmental mandibulectomy with reconstruction using composite free-tissue transfer results in similar post-operative QOL scores as rim resection [34].…”
Section: Qol and Reconstructionmentioning
confidence: 98%
“…Two patients required a revision of the donor site defect with a further skin graft. Microsurgical vascularised osteo-myocutaneous free flaps are very useful for reconstruction of complex defects following maxillectomy and mandibulectomy [15,16]. Both iliac crest and fibula free flaps can be considered the best option for mandibular reconstruction [15,16].…”
Section: Discussionmentioning
confidence: 99%